The population dynamics of Middle Saxon East Anglia: a multi-isotope and geochemical study - Moore, Fiona E. (2023)
This thesis presents a multiple isotope examination of mobility and dietary intake of three Middle Saxon populations drawn from the region of eastern England, broadly analogous to the Anglo-Saxon Kingdom of East Anglia. The centuries from AD 650 to 850 were a period of economic transformation, reflected in the appearance of new site types prominent in the archaeological record, in particular emporia and high-status estate centres. Scholarship has suffered from ‘top down’ interpretations of economic development, obscuring the rural populations who appear to have been the true agents of progress.